Study and Analysis of Developments in ChatGPT and Impact on Humanity - Suryakant Kulkarni; K.T. Madrewar (International Journal of Mobile Computing Technology, 2024)
This research paper examines the ChatGPT model of Artificial Intelligence, including its architecture, training process, applications, issues, and future advancements. ChatGPT employs a transformer-based design and undergoes pre-training and fine-tuning procedures. Its applications are conversational AI, translation, content generation, and research. In the real world, you can find it helping in online shops, banks, hospitals, and customer service. We also want to make sure it treats everyone fairly, stays safe, and respects users’ privacy. Even though it is perfect at conversations, there are still some issues like biases, safety concerns, and making sure it talks in a way everyone can understand. To ensure the responsible and efficient deployment of Chat GPT, future research should concentrate on improving these issues.
Keywords: ChatGPT; NLP; OpenAI; chatbot; generative pre-trained transformer (GPT); transformer neural network